CAFF CBMP Report No. 20 - Arctic Species Trend Index 2010: Tracking Trends in Arctic Wildlife. - McRae, Louise; Gill, Michael; Zöckler, Christoph; Loh, Jonathan; Latham, Julia; Harrison, Nicola; Martin, Jenny; Collen, Ben (CAFF International Secretariat, 2010)
The contribution of Arctic wildlife to global biodiversity is substantial. The region supports globally significant populations of birds, mammals and fish.In this report, vertebrate population-abundance data were used to produce an indicator of the trends in Arctic biodiversity over the past 34 years (1970 as the baseline1). This index tracks 965 populations of 306 species, representing 35% of all known vertebrate species found in the Arctic. These observed trends are largely consistent with current predictions regarding the response of Arctic wildlife to climate change and expected increases in previously over-harvested species, and suggest that human-induced changes in Arctic ecosystems are already resulting in winners and losers.